Dynamic spreading process of water on coal and its micro wetting mechanism under different gas environments - Leilei SI; Yihan GU; Jianping WEI; Nan DING; Wan JIANG; Banghua YAO; Zhihui WEN (Meitan xuebao)
Coal seam water injection is a comprehensive mine disaster prevention and control measure, and the wetting and spreading of water solution on the coal surface is a dynamic process. Especially when the coal seam contains a certain amount of gas, the environmental pressure and adsorption effect will further affect the dynamic wetting and spreading law of coal and water. Therefore, it is necessary to deeply analyze the dynamic wetting mechanism of gas-containing coal to provide theoretical guidance for coal seam water injection. In this paper, a dynamic contact angle measurement system for gas-containing coal was built, and experiments on the dynamic change law of the contact angle of water on coal under different gas environments (adsorptive gases CO2 and CH4 and non-adsorptive gas He) were carried out. Molecular dynamics simulation was used to analyze the dynamic change law of the contact angle of water on coal from the microscopic scale under different gas environments, and the dynamic wetting and spreading process of water on coal under normal pressure and three different gas conditions was analyzed. The results show that the dynamic wetting and spreading process of water on coal can be divided into three stages: easy spreading stage, slow spreading stage and stable equilibrium stage. With the increase of gas pressure and adsorption performance, the liquid spreading rate decreases and the difficulty of coal wetting increases. Both the experimental and molecular dynamics simulation results show that under normal pressure conditions, the shape of water molecules is relatively flat. With the increase of gas pressure and adsorption capacity, the difficulty of water solution spreading increases, and the shape of the droplet gradually approaches an ellipse or a half-sphere. In the adsorptive gas environment, a gas adsorption layer is formed on the coal surface, and as the gas pressure and adsorption capacity increase, the thickness of the adsorption layer increases, making it difficult for the water solution to break through the gas adsorption layer and thus unable to wet the micro-pores. By analyzing the change law of the surface free energy of coal under different gas environments, it is found that with the increase of gas adsorption performance and environmental pressure, the coal molecules tend to be stable by capturing gas molecules to reduce their own energy, that is, the surface free energy gradually decreases, and the coal surface system becomes relatively more stable, making it difficult for the water solution to spread and wet on the coal surface, thereby weakening the wetting effect of coal and water. The research results can provide certain theoretical guidance for the water injection wetting of gas-containing coal.